Essays on international law - Baber, Graeme (Cambridge Scholars Publishing, 2017)
This book contains ten writings on different aspects of international law, each of them cross-referenced, in instances in which information in one is relevant to points made in another. The first essay considers the character of the subject, and its relation to other entities of relevance to it, such as its compatibility with national law and its relation to maritime law. The second one considers different types of legal instruments in settings of international law, and explains how to read a multilateral convention, using the Convention for the International Sale of Goods as an example. The t.